2001
DOI: 10.1177/106689690100900402
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Quantitative Analysis of E-cadherin Expression in ret/PTC-1-Activated Thyroid Neoplasms

Abstract: Papillary thyroid carcinoma (PTC), the most common variety of thyroid cancer, is found in a variety of morphologic variants, usually grows slowly, and is clinically indolent, although rare, aggressive forms, with local invasion or distant metastases, occur. Our group has previously demonstrated an association between Hashimoto thyroiditis and ret/PTC-1 activation, and have hypothesised that c-ret activation might be implicated in immune reaction to thyroid epithelium. The objective of this study was to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
13
2
2
Order By: Relevance
“…Contrary to our data and above-mentioned studies, Smyth et al demonstrated a significant reduction of E-CAD expression in FC when compared to normal thyroid or FA but not a significant diminution of E-CAD expression in PTC [38].…”
Section: Discussioncontrasting
confidence: 86%
“…Contrary to our data and above-mentioned studies, Smyth et al demonstrated a significant reduction of E-CAD expression in FC when compared to normal thyroid or FA but not a significant diminution of E-CAD expression in PTC [38].…”
Section: Discussioncontrasting
confidence: 86%
“…Monaco et al (25) speculate that protein interactions, mediated by protein products of the genes fused to ret at the 5Ј terminal (H4 and ELE-1), affect the signaling of the specific ret/PTC isoforms. We have previously demonstrated consistently reduced expression of E-cadherin in ret/PTC-1-positive cohorts in comparison with normal thyroid tissue (26). A comparable study assessing expression levels of E-cadherin in ret/PTC-3-positive and -negative normal controls failed to demonstrate a significant reduction (Smyth, P., S. P. Finn, and O. Sheils, unpublished data).…”
Section: Discussionmentioning
confidence: 81%
“…CDH1 expression is decreased in classic papillary thyroid carcinoma 3,6 -10 and its diffuse sclerosing variant 9 and also in follicular carcinoma. 3,7,8,[11][12][13] Rarely, this decrease in expression is attributable to mutation of the CDH1 gene, 7,9 loss of heterozygosity, 7 or hypermethylation of the CDH1 promoter. 9 In most tumors the mechanism of CDH1 down-regulation is, however, unknown.…”
mentioning
confidence: 99%